2012
DOI: 10.1111/j.1365-2265.2011.04279.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and therapy for Cushing’s disease with negative dynamic MRI finding: a single‐centre experience

Abstract: Based on the findings outlined, MRI-negative CD may be a surgically remediable syndrome, with a pathophysiological basis that primarily involves a pituitary cause of the hypercortisolaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
2
15
1
6
Order By: Relevance
“…Previous authors have also reported the lower remission rates we found with negative histology (15,20,22,41,42): this has been recently confirmed in a large study (15). Regarding imaging studies, we found no difference in remission rates between groups with negative or positive imaging, in concordance with both older and more recent studies that focused only on these two subgroups (43,44), as well as with most other previous studies (17,22,42). This is not especially surprising, as microadenomas are often not visible on MRI, whereas pituitary incidentalomas are found in 10% of the normal population (45).…”
Section: Remission Ratessupporting
confidence: 80%
“…Previous authors have also reported the lower remission rates we found with negative histology (15,20,22,41,42): this has been recently confirmed in a large study (15). Regarding imaging studies, we found no difference in remission rates between groups with negative or positive imaging, in concordance with both older and more recent studies that focused only on these two subgroups (43,44), as well as with most other previous studies (17,22,42). This is not especially surprising, as microadenomas are often not visible on MRI, whereas pituitary incidentalomas are found in 10% of the normal population (45).…”
Section: Remission Ratessupporting
confidence: 80%
“…Pituitary stalk interruption syndrome, first described as transection of PS in 1987, gets more recognition these years due to the fact that MRI is routinely performed in patients suspected of pituitary diseases. In our study involving 74 adult patients, the age at diagnosis was 25 (22)(23)(24)(25)(26)(27)(28) years, significantly older than 3Á6 years by Gascoin-Lachambre et al, 28 4Á0 years by Pinto et al 1 and 19Á7 years by Guo et al, 29 which made our population different than previously reported. We assumed atypical onset symptoms, negligence of short stature at early ages and insufficient understanding of the disease might attribute to this phenomenon to some extent.…”
Section: Discussioncontrasting
confidence: 70%
“…Although HC has been successfully used to treat keloids, it also induces certain adverse effects, such as arthralgia ( 39 ). In the present study, 9 small molecule drugs were identified by the CMAP database and acemetacin was predicted to be the most effective drug at reducing the adverse effects of HC.…”
Section: Discussionmentioning
confidence: 99%